INTERPERSONAL COMMUNICATION STRATEGIES IN THE LISTENING PROCESS DURING THE COVID 19 PANDEMIC (DEPOK CITY RESIDENTS) - Radjagukguk , Djudjur Luciana (International Peneliti Ekonomi, Sosial dan Teknologi, 2021)
Good communication is needed in conveying messages, one of which is interpersonal communication or what is called interpersonal communication (interpersonal). This is done by individuals to exchange ideas or thoughts in other words to hear what is being said. Interpersonal communication can be done in verbal and nonverbal forms, not only about what is said and what is received. But how it is said, in the body language used, and the facial expressions that are given. This is very much needed during the Covid 19 pandemic, so that residents of Depok City can be given messages directly on their understanding of Covid 19.. The purpose of this study was to identify and describe interpersonal communication strategies in the listening process to Depok residents during the Covid 19 pandemic. The research method used was through observation and in-depth interviews with the Task Force. The results of the research by residents of Depok City understand and want to carry out what the Depok government hopes are by obeying what was done and not done during the Covid 19 pandemic. In addition, the participation of the community takes part in overcoming the problems that befell the Indonesian nation, especially the citizens of Depok City.